Cholemic Nephrosis: An Autopsy Study of a Forgotten Entity - Valli PRIYAA; Bheemanathi Hanuman SRINIVAS; Debasis GOCHHAIT; Rajesh NACHIAPPA GANESH; Bhawana A BADHE; PS PRIYAMVADA; Deepak AMALNATH; Siddhartha DAS; Kusa Kumar SHAHA (Federation of Turkish Pathology Societies, 2021)
Objective: The aim of the study is to do a clinicopathologic study of post mortem kidney biopsies with significant deposition of bilirubin pigment within tubular epithelial cells and in the lumen of distal tubules as a bile cast. Material and Method: All post mortem specimens with acute tubular necrosis, with the presence of bile casts in tubules or bile pigment deposition in the tubular epithelium during the period 2015-2018 were examined for gross and histopathology along with biochemical parameters and viral markers. Results: Bile casts with sloughed renal tubular epithelial cells and occasional macrophages were present in the distal convoluted tubule in 78.6% of biopsies (11/14). The plugging of distal convoluted tubule with casts was similar to that seen in myeloma and myoglobin cast nephropathies. Bilirubin pigment deposition was present in 35.7% (5/14) of cases. The frequency of bile casts in each biopsy was variable and it did not have any association with serum bilirubin levels or etiology of liver dysfunction. A striking difference from earlier studies is the high number of toxin-induced liver damage including six cases of paraquat and 2 cases of yellow phosphorus poisoning. Conclusion: This study proves importance of the bile cast nephropathy as a reason for kidney injury, especially with varied hepatotoxic etiologies, especially paraquat and yellow phosphorus.